Casino resort industry & corporate governance - Neo, Tingyuan (2008)
The objective of this study is to analyze the performance of the casino resorts industry in the United States and Asia Pacific region, and also to study the corporate governance structure in the casino resorts industry in the two regions. The first part of our study provides investors an overview of the performance of both United States and Asia-Pacific industries. The second part of our study seeks to address concerns about the corporate governance standards in the casino resorts industry in the two regions. We attempt to measure and compare corporate governance in the firms by developing a G-score for twenty-three publicly listed firms in United States and ten publicly listed firms in Asia-Pacific casino resorts industries for two years, 2005 and 2006.